Posttraumatic stress, psychological morbidity, psychopathology, family functioning and quality of life in portuguese war veterans - Pereira, M. Graça (2012)
Thirty-four years after the end of Colonial War, few data are available on the impact of such experience on Portuguese veterans. The purpose of the present study was to assess post-traumatic stress disorder (PTSD), psychological morbidity, psychopathology, family functioning, and quality of life in veterans with and without PTSD diagnosis, to find the best predictors of quality of life and to analyse psychopathology as a mediator in the relationship between traumatic symptoms and quality of life. A total of 101 male veterans participated in the study. Veterans were recruited from a central hospital and a veterans organization. The instruments used were the Portuguese versions of Posttraumatic Stress Scale (McIntyre & Ventura), FACES III (Olson, Portner, & Lavee), BSI (Derogatis), BDI (Beck, Ward, Mendelson, Mock, & Erbaugh), STAI (Spielberger, Gorush, Lushene, Vagg, & Jacobs), and Quality of Life (WHOQOL Group). Results showed quality of life to be significantly related to less depression and anxiety. Veterans with PTSD diagnosis had more psychopathology and less quality of life in all domains. Veterans who belonged to extreme families showed more psychopathology and presented more PTSD symptoms, particularly avoidance and intrusion. When all psychological variables entered in the regression model, depression predicted physical quality of life; trait anxiety predicted psychological quality of life; PTSD predicted social quality of life; and, depression predicted environmental quality of life. Finally, psychopathology was a mediator of the relationship between traumatic symptoms and all domains of quality of life except environmental quality of life. Results emphasize the need for psychological interventions in veterans and their families.